James Predergast and the Treaty of Waitangi: Judicial Attitudes to the Treaty During the Latter Half of the Nineteenth Century - Morris, Grant (Victoria University of Wellington Law Review, 2004)
Chief Justice James Prendergast has largely been demonised over the last two decades as a result of his famous decision in the Wi Parata v The Bishop of Wellington case in 1877. In that decision, he notably stated that the apparent cession of sovereignty in the Treaty of Waitangi was "a simple nullity". This statement has effectively taken on a life of its own, and is still cited – with polarising effect – in the current debate on the place of the Treaty in modern New Zealand society. The author argues, however, that the debate and commentary on the case has largely omitted to consider Prendergast as a man of his times and background and as an important part of a small legal community. The part that others had to play in the Wi Parata case is often not mentioned, for example. This article seeks to redress the balance somewhat. In doing so, it does not underestimate the devastating effect which the decision had in supporting the alienation of Maori land. However it emphasises that Prendergast's view represented the orthodoxy of the time, and for some considerable time thereafter, and that his main fault was that he failed to rise above the prejudices of the settler society in which he lived.